2009
DOI: 10.3892/or_00000539
|View full text |Cite
|
Sign up to set email alerts
|

A traditional Chinese medicine formulation consisting of Rhizoma Corydalis and Rhizoma Curcumae exerts synergistic anti-tumor activity

Abstract: Abstract. Synergy analysis of anticancer agents is an important approach to determining the ratio and/or dose of drugs for clinical combination therapy. However, this method is rarely used to evaluate the composition of traditional Chinese medicine formulation. 'Yanhusuo San' (YHSS), which consists of yanhusuo (Rhizoma Corydalis) and Ezhu (Rhizoma Curcumae), has been an archaic Chinese medicine prescription since the Song dynasty (960-1279 AD). We previously demonstrated that either yanhusuo or ezhu has strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In addition to western therapies for cancer prevention, there are also studies on anti-tumor effects of herbal medicines such as D. bulbifera, Tripterygium wilfordii, and Andrographis paniculata (Shamon et al, 1997;Gao et al, 2002;Kumar et al, 2004). Compatibility is a main principle of Chinese medicinal herbs, and some reports have demonstrated that compatibility may lead to eliminating toxicity or reinforcing bioactivities (Kim et al, 2007;Gao et al, 2009). Ferulic acid is the main bioactive component of A. sinensis root, and our results from ALT/AST assays and histological observations are the first to demonstrate that ferulic acid prevents diosbulbin B-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to western therapies for cancer prevention, there are also studies on anti-tumor effects of herbal medicines such as D. bulbifera, Tripterygium wilfordii, and Andrographis paniculata (Shamon et al, 1997;Gao et al, 2002;Kumar et al, 2004). Compatibility is a main principle of Chinese medicinal herbs, and some reports have demonstrated that compatibility may lead to eliminating toxicity or reinforcing bioactivities (Kim et al, 2007;Gao et al, 2009). Ferulic acid is the main bioactive component of A. sinensis root, and our results from ALT/AST assays and histological observations are the first to demonstrate that ferulic acid prevents diosbulbin B-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Viability assays revealed that germacrone could inhibit cell proliferation in the dose-and treatment time-dependent manner in BGC823 cells. As the anti-tumor capabilities of Rhizoma curcuma have been identified clinically in China [30], findings in the present study are inspiring for future studies on investigating the bioactivities of other volatile oil components isolated from Rhizoma curcuma, such as β-elemene, curcumol, curdione, neocurdione, etc.…”
Section: Discussionmentioning
confidence: 69%
“…Corydalis yanhusuo (YHS) is a common TCM drug pair that can be used to treat tumors 4 . According to previous research, the active ingredient in YHS is Dehydrocorydaline, which can suppress cell growth, invasion, and migration by inhibiting the MEK1/2-ERK1/2 cascade within melanoma 5 .…”
Section: Introductionmentioning
confidence: 99%